(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Vocational education aims to provide learners with practical skills, professional competencies, and the ability to adapt to modern labor market demands. Among various vocational practices, sewing children’s clothing offers a comprehensive platform for skill development, encompassing technical, cognitive, and social competencies. This paper examines the role of children’s clothing sewing in vocational education, exploring pedagogical strategies, the spectrum of skills acquired, and associated benefits and challenges. Drawing on contemporary literature and educational practices, it argues that sewing activities not only enhance technical proficiency but also foster creativity, problem-solving, teamwork, and reflective thinking, ultimately equipping learners for professional and entrepreneurial success.